Bonding mechanism of explosive compaction–welding sintering. (October 2019) - Chen, Xiang; Li, Xiaojie; Wang, Xiaohong; Yan, Honghao; Li, Kebin; Zeng, Xiangyu
Abstract: Correlation theories of explosive compaction–welding sintering are introduced, and a method for calculating the pressure required for explosive compaction–welding is provided. A macroscopic bonding mechanism study involving a flying-plate loading experiment reveals that the incident angle of a shockwave plays an important role in explosive compaction–welding, and the propagation law of shockwaves in powder layers is numerically analyzed using the AUTODYN-2D software. In the microscopic bonding mechanism study, the microscopic bonding modes of explosive compaction–welding are investigated with a Cu wire coating and Cu substrate. The smoothed-particle hydrodynamics numerical simulation method is used to simulate the void-closure process between the Cu wire and Cu substrate under specific pressures. By comparing the results of the numerical simulation and experiment, the micro-bonding modes of friction welding, explosive welding, jet injection, and liquid sintering are determined. The effect of diffusion sintering is studied, and the poor bonding areas are eliminated after diffusion sintering. The element diffusion between the coating and substrate is observed to ensure the existence of diffusion welding.